Получение нанопорошка состава 85 вес.% Al₂O₃ + 15 вес.% ZrO₂(Y₂O₃) методом совместного осаждения - Шкуропатенко, Владимир Антонович (НТУ "ХПИ", 2016)
Нанокристаллический порошок состава 85 вес.% Al₂O₃ + 15 вес.% ZrO₂(Y₂O₃) синтезирован методом совместного осаждения с последующей термообработкой. Определены фазовый состав и размеры частиц порошка на разных стадиях термообработки. После термообработки при температуре 1200 °С фазовый состав полученного порошка представлен корундом α-Al₂O₃ и тетрагональным оксидом циркония t-ZrO₂ размер частиц порошка корунда составляет ≈ 45 нм и тетрагонального оксида циркония ≈ 35 нм. Показано взаимное влияние частиц оксида алюминия Al₂O₃ и оксида циркония ZrO₂(Y₂O₃) на скорость роста порошка состава 85 вес.% Al₂O₃ + 15 вес.% ZrO₂(Y₂O₃) при термической обработке. Установлено, что присутствие тетрагонального оксида циркония после термической обработки при 1200 °С предопределяется наличием наноразмерных частиц полученного порошка состава 85 вес.% Al₂O₃ + 15 вес.% ZrO₂(Y₂O₃) и стабилизирующим действием введенного в оксид циркония оксида иттрия.

Nanocrystalline powder of 85 wt.% Al₂O₃ + 15 wt.% ZrO₂(Y₂O₃) composition was synthesized by co-precipitation followed by heat treatment process. The phase composition and particle size of the powder at various stages of the heat treatment were determined. It was shown that the size of primary particles of obtained powder after co-precipitation and thermal treatment processes at temperatures 600 and 800 °С was about 4-5 nm. After treatment temperature increasing to 1000 °С the size of the primary particles was grown up to 9-10 nm. It was demonstrated that the powder of the investigated composition is presented mainly by X-ray amorphous phase both after co-precipitation and thermal treatment processes at temperatures 600 and 800 °С during 2 hours. The temperature increasing to 1000 °С leads to more intensive crystallization and at temperature 1200 °С amorphous phase is substituted by crystalline phase. The phase composition of produced powder after heat treatment at temperature 1200 °С was presented by phases of corundum α-Al₂O₃ and tetragonal zirconia t-ZrO₂, particle size of the powder of corundum α-Al₂O₃ ≈ 45 nm and tetragonal zirconia t-ZrO₂ ≈ 35 nm. The cross-coupling of alumina Al₂O₃ and zirconia ZrO₂(Y₂O₃) particles on speed of powder growth of 85 wt.% Al₂O₃ + 15 wt.% ZrO₂(Y₂O₃) composition at heat treatment is shown. It is set that presence of tetragonal zirconia after heat treatment at 1200 °C predetermined by the presence of nanosize particles of the obtained powder of 85 wt.% Al₂O₃ + 15 wt.% ZrO₂(Y₂O₃) composition and stabilized action of the yttrium oxide entered in the zirconia.
Producing of nanopowder of 85 wt.% Al₂O₃ + 15 wt.% ZrO₂(Y₂O₃) composition by co-precipitation method
Keywords: нанокристаллический порошок; совместное осаждение; корундо-циркониевая керамика; рентгенофазовый анализ; дифференциально-термический анализ; nanocrystalline powder; coprecipitating; corundum-zirconia ceramics; X-ray diffraction; differential thermal analysis